Showdown in Schönau: a contest case study - Dijkstra, Bouwe R.; Graichen, Patrick R. (Springer, 2017)
This chapter analyzes a referendum campaign as a case study of a contest. The referendum, held in 1996 in the small German town of Schönau, led to the replacement of the convention-al electricity supplier by a firm founded by the local environmentalists. We discuss both quali-tative aspects (activities, arguments and strategies of the environmentalists, the electricity firm and its local allies) and quantitative aspects (lobbying effectiveness, stakes, effort and success probability). We identify voter groups more inclined to vote one way or the other and factors that contributed to the environmentalists’ victory. Finally, we discuss modeling implications.